ROMANIAN HIGHER EDUCATION SYSTEM IN CONTEXT OF GLOBALIZATION - Asser KHAMIS (Business Excellence and Management, 2017)
An institutional system timetable for performance evaluation and quality control within higher education institutions is done for higher education institutions to carry out a periodical self-assessment study for development engagements for maximizing points of strength and improving points of weaknesses based on the selfassessment reports recommendations and feedback. Research collaborations are clearly focus priority for institutions large, while the mobility of outgoing students is in first place for small institutions.